2005
DOI: 10.1103/physrevlett.94.017203
|View full text |Cite
|
Sign up to set email alerts
|

Antisymmetric Magnetoresistance in Magnetic Multilayers with Perpendicular Anisotropy

Abstract: While magnetoresistance (MR) has generally been found to be symmetric in applied field in non-magnetic or magnetic metals, we have observed antisymmetric MR in Co/Pt multilayers. Simultaneous domain imaging and transport measurements show that the antisymmetric MR is due to the appearance of domain walls that run perpendicular to both the magnetization and the current, a geometry existing only in materials with perpendicular magnetic anisotropy. As a result, the extraordinary Hall effect (EHE) gives rise to ci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
52
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 25 publications
10
52
1
Order By: Relevance
“…Recently, it was shown that a minor variation of the thickness along the sample can induce this effect [28], but similar effects were also found at magnetization reversal of ferromagnets with an out-of plane magnetic anisotropy and explained by the movement of a domain wall located between the voltage probes, running perpendicular to both magnetization and current [29]. …”
Section: Resultsmentioning
confidence: 92%
“…Recently, it was shown that a minor variation of the thickness along the sample can induce this effect [28], but similar effects were also found at magnetization reversal of ferromagnets with an out-of plane magnetic anisotropy and explained by the movement of a domain wall located between the voltage probes, running perpendicular to both magnetization and current [29]. …”
Section: Resultsmentioning
confidence: 92%
“…[5][6][7] The domain-wall motion mode dominates in the Pt/ Co/ Pt trilayers or ͓Co/ Pt͔ n multilayers with very small n, resulting in magnetically uniform bubble domains with changing sizes. 8,9 In contrast, the behavior of the ͓Co/ Pt͔ 4 multilayers with an intermediate n is between the above two limiting cases. When H is decreased from the positive saturation to −H T ͑point 2 in Fig.…”
Section: C905-2mentioning
confidence: 86%
“…5 At the other extreme, thin Pt/ Co/ Pt trilayers revealed very different behaviors, where magnetic domains expand by the propagation of smooth and well-defined domain walls. 8,9 Under a reversed field, the domain walls retract toward the nucleation centers. However, there has been little work on ͓Co/ Pt͔ n multilayers with an intermediate n, although several papers reported other materials with PMA and intermediate thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid increase in the memory operation frequency in modern computers and applications of ferromagnetic films to the microwave devices motivated special interest in their high-frequency dynamics [1,2]. Nowadays much attention is paid to thin multilayers deposited on silicon substrate [3][4][5]. From the application viewpoint, the knowledge of elastic properties of nanometric materials is of particular importance.…”
Section: Introductionmentioning
confidence: 99%